Chemical and thermal properties of VO2 mechanochemically derived from V2O5 by co-milling with paraffin wax. Issue 38 (11th June 2018) - Takai, Chika; Senna, Mamoru; Hoshino, Satoshi; Razavi-Khosroshahi, Hadi; Fuji, Masayoshi
Abstract : Reduction of V2 O5 via a mechano-chemical route brings about unique electronic states of vanadium. The resulting VO2 exhibits high latent heat storage during heating (a) and cooling (b). Abstract : A novel mechanochemical reduction process of V2 O5 to VO2 was established by milling with paraffin wax (PW, average molecular weight 254–646), serving as a reductant. The reduction progressed with increasing milling time and mass ratio V2 O5 : PW (MRVP). The mechanochemically derived VO2 became phase pure after milling for 3 h with an MRVP of 30 : 1 and exhibited a reversible polymorphic transformation between tetragonal and monoclinic phases at around 53–60 °C and 67–79 °C during heating and cooling, respectively. The latent heat was above 20 J g −1 in both processes, being superior to those of commercial VO2 . Doping of starting V2 O5 with Cr, Mo or W at 1 at% in the form of oxide did not increase the latent heat. This is another difference from the conventionally prepared doped VO2 . These anomalous heat storage properties of mechanochemically derived VO2 were discussed mainly on the basis of X-ray photoelectron spectroscopy V2p3/2 peaks combined with ion etching. The observed relatively high heat storage capacity of undoped VO2 is primarily ascribed to the abundance of V 4+ ionic states introduced during milling with PW, which were stabilized with simultaneously introduced structural degradation throughout the entire particles. The possible role of a remaining small amount of PW was also discussed.